Understanding Chinese mobile social media users' communication behaviors during public health emergencies. Issue 7 (1st August 2022) - Wang, Houcai; Xiong, Li; Wang, Chengwen; Chen, Nan
Abstract: Mobile social media has become a significant platform for information exchange and social interaction during public health emergencies, and it has experienced exponential growth during the COVID-19 pandemic. The pandemic has forced many emergency agencies to rethink the way emergency information is disseminated. Mobile social media can be applied to public health emergency response, and it has great potential value as a tool for fostering government-citizen relationships during public health emergencies. Furthermore, consideration of specific risk cultures and rigorous censorship of social media may influence citizens' use of mobile social media during the pandemic or other public health emergency. Thus, to investigate the specific mobile social media communication behaviors of Chinese citizens during the COVID-19 pandemic, we surveyed 2, 074 mobile social media users in China from February to August 2020. We found that the state-oriented risk culture and strict censorship of social media, influence Chinese mobile social media users to seek and share information about the pandemic during public health emergencies; this finding has practical implications and academic value, because it increases the understanding of mobile social media users' communication behaviors, supports shared situational awareness, and increases social resilience when responses to public health emergencies.